Keterlibatan Siswa dalam Pembelajaran Bahasa Arab: Studi di Lingkungan Formal - Mas’ud; Muhammad Tareh Aziz (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This study examines student engagement in Arabic language learning at SMA N 2 Sumenep, focusing on factors influencing participation and their impact on academic outcomes. Findings reveal significant variability in student engagement levels, with active participants demonstrating better understanding and higher motivation compared to passive ones. Key internal factors affecting engagement include personal motivation and language proficiency, while external factors such as teaching methods and classroom environment also play crucial roles. Interactive teaching methods and supportive learning environments were found to enhance student participation. The study underscores the importance of addressing both internal and external factors to improve student engagement. By adopting more engaging teaching strategies and fostering a conducive classroom atmosphere, educators can enhance student involvement and academic performance in Arabic language education. This research provides valuable insights for refining teaching practices and optimizing student learning experiences in Arabic language programs.